Dostoevsky's Crime and punishment : a reader's guide - Martinsen, Deborah A. (Cultural syllabus., 2022)
"A chapter-by-chapter guide to Dostoevsky's most popular novel that reveals how "Crime and Punishment" works. Narrative strategy, why the novel is not a "whodunit" but "whydunit," and clear explanations of the novel's ideological debates"--